Real-Time Quaking- Induced Conversion Assays for Prion Diseases, Synucleinopathies, and Tauopathies - Vascellari, Sarah; Orrù, Christina D.; Caughey, Byron (Frontiers in Aging Neuroscience, 2022)
Prion diseases, synucleinopathies and tauopathies are neurodegenerative disorders characterized by deposition of abnormal protein aggregates in brain and other tissues. These aggregates consist of misfolded forms of prion, α-synuclein, or tau proteins that cause neurodegeneration and represent hallmarks of these disorders. A main challenge in the management of these diseases is the accurate detection and differentiation of these abnormal proteins during the early stages of disease before the onset of severe clinical symptoms. Unfortunately, many clinical manifestations may occur only after neuronal damage is already advanced and definite diagnoses typically require postmortem neuropathological analysis. Over the last decade, several methods have been developed to increase the sensitivity of prion detection with the aim of finding reliable assays for the accurate diagnosis of prion disorders. Among these, the real‐time quaking‐induced conversion (RT–QuIC) assay now provides a validated diagnostic tool for human patients, with positive results being accepted as an official criterion for a diagnosis of probable prion disease in multiple countries. In recent years, applications of this approach to the diagnosis of other prion-like disorders, such as synucleinopathies and tauopathies, have been developed. In this review, we summarize the current knowledge on the use of the RT-QuIC assays for human proteopathies.